Assessment of soil quality monitoring indicators under long term rice cultivation in hot arid Ghaggar-flood plains of India. Issue 14 (6th December 2018) - Moharana, Pravash Chandra; Singh, Ram Sakal; Singh, Surendra Kumar; Jena, Roomesh Kumar; Naitam, Ravindra Kashinath; Verma, Thakur Prasad; Nogiya, Mahaveer; Meena, Roshan Lal; Gupta, Dipak Kumar; Kumar, Sunil; Tailor, Bhagwati Lal; Singh, Rameshwar
ABSTRACT: The evaluation of soil quality is essential in monitoring the long term effects of rice cultivation. Present study investigated the effects of long term rice cultivation on soil properties and organic C pools and identified indicators for monitoring soil quality in Ghaggar-flood plains of hot arid India. Soil samples were collected from fields with 0, 10, 20, 30 and 40 years of rice cultivation. The study revealed that electrical conductivity (EC) and exchangeable sodium percentage (ESP) increased after 30–40 years of rice cultivation. Available nutrients increased with increasing years of rice cultivation. The organic carbon pools namely, total organic carbon (TOC), Walkley Black carbon (WBC) and particulate organic carbon (POC) were increased above 50% in 20 and above years of rice cultivation. The TOC and POC were increased by 40.6 to 132.4% and 31.7% to 104.8% in 10 to 40 years of rice cultivation. Cation exchange capacity, WBC, ESP and CaCO3 could serve as soil monitoring indicators of long term rice cultivation in arid region. The findings clearly indicated that long term rice cultivation could aggravate soil salinity and have negative impact on soil quality in arid environment.